KINERJA ANGGOTA BPD DI KECAMATAN LASEM DAN PERAN YANG MEMPENGARUHINYA - Andriano, Khanda Eka Meylana; Ilhami, Susanti Dwi (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
An institution is said to be successful by observing the performance of its employees in carrying out the roles and responsibilities assigned to them. This study was conducted to demonstrate the impact of work motivation, work discipline, and communication on the performance of members of the Village Consultative Body in Lasem District. The research population involves 144 BPD employees in Lasem District, with the entire population being the research sample. (sampel jenuh). Data were collected using a questionnaire. Multiple linear regression analysis serves as a tool for analyzing and presenting results. These findings show that the variables of work motivation and communication have a significantly positive effect on the performance of BPD members in Lasem District, while the work discipline variable has a positively insignificant effect on the performance of BPD members in Lasem District. The findings from the determination test explain that 43.1% of the observed independent variables can explain the dependent variable, while the remaining 66.9% is explained by variations in other variables not discussed in this study.